Investigating the Effects of Training Length on Wrestlers' Musculoskeletal Strength - Hidayatulloh, Moh. Tedo Khairun; Sumartiningsih, Sri (Media Ilmu Keolahragaan Indonesia, 2023)
The objective was to explore the relationship between the duration of training sessions and the resulting strength in arm, leg, and back muscles among wrestlers in Kendal Regency. Recognizing a gap in existing literature regarding sport-specific training duration, this study aimed to establish whether a correlation exists between training duration and musculoskeletal strength improvements. Utilizing a combination of interviews for exercise duration data and push pull and back leg dynamometers for measuring muscle strength, the study comprised a sample of wrestlers with a mean age of 17 years. Statistical analysis, including the Shapiro-Wilk test for normality, revealed that the data were normally distributed, allowing for considerations of correlation. Results demonstrated a significant relationship between training length and muscle strength gains, signifying the beneficial effects of individualized training durations on specific muscle strength development in wrestlers. These findings highlight the necessity of personalizing training plans to harness the full potential of strength conditioning in athletes and informing more effective training practices moving forward